Design and build a regulated dc supply - Wong, Liang Wei (2015)
A regulated direct current (DC) power supply was designed, built and embedded in a circuit. It helps to converts unregulated alternative current (AC) source to a constant DC source with the aid of rectifier. The rectifier were constructed with diodes and capacitors which subsequently passed the unregulated output through a regulator circuit. It is to supply a stable output (voltage or current) to a device with specific operating power supply limits. The final output of the regulated power supply will consist of negligible AC signal that is caused by the ripple voltage. A regulated DC power supply was designed and built in this hardware construction project. Rectifier Circuit was developed to obtain DC voltage from a stepped down AC voltage and ripple voltage analyzed and discussed based on the theoretical prediction/was studied on a theoretical basis. A voltage regulator was built using discrete component to produce a stable DC power supply with negligible ripple voltage.